Carcass characteristics of Garag sheep in the White vile State, Sudan - E. Elimam, Mohmed; A. A. Bashir, Abdellatif; M. A. Mudawi, Tilal (المجلة الزراعية; مجلد 10 عدد 2 (2012), 2023)
SHORT NOTE Sheep production is very important in the Sudan as it is widely distributed and has socio-economic impacts (Ministry of Animal Resources and Fisheries, 2004). Sheep exports are increasing due to premium quality and are fed natural pastures with no feed additives, especially of animal origin, or growth promoters which threaten human and livestock health.